2021
DOI: 10.3390/nano11040963
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Characteristics of Pristine and Magnetic Olive Stones Biochar with Respect to Clofazimine

Abstract: Olive stone biochars (OSBC), both pristine and following magnetization (MAG–OSBC), were utilized as eco-friendly and cost-effective sorbents for the antituberculosis, clofazimine (CLOF). Morphologies, textures, surface functionalities, and thermal stabilities of both adsorbents were explored using SEM, EDX, TEM, BET, FT-IR, Raman, XRD and TGA analyses. SEM analysis showed meso- and macroporous surfaces. BET data showed that the MAG–OSBC possesses a larger surface area (33.82 m2/g) and pore volume. Batch adsorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 64 publications
4
16
0
Order By: Relevance
“…The pH PZC of the as-prepared samples, Figure 2 c revealed that OSBC has a pH PZC of 5.1 and changed to 6.8 following the impregnation with the Co 3 O 4 nanoparticles. These values are comparable to the previously reported values for OSBC [ 37 , 54 ]. As a result, at a pH of 5.0 ± 0.2 (lower bound), the surface of the adsorbent could be neutral to positively charged, but at a pH of 9.0 ± 0.2 (upper bound), the surface will be negatively charged.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The pH PZC of the as-prepared samples, Figure 2 c revealed that OSBC has a pH PZC of 5.1 and changed to 6.8 following the impregnation with the Co 3 O 4 nanoparticles. These values are comparable to the previously reported values for OSBC [ 37 , 54 ]. As a result, at a pH of 5.0 ± 0.2 (lower bound), the surface of the adsorbent could be neutral to positively charged, but at a pH of 9.0 ± 0.2 (upper bound), the surface will be negatively charged.…”
Section: Resultssupporting
confidence: 91%
“…Biochar of olive stones (OSBC) either pristine or engineered has recently garnered the attention as an adsorbent for removing aquatic contaminants [ 35 , 36 , 37 ]. Conversion of olive stones into BC-based adsorbent is a sustainable solution for the disposal problems confronted by the well-established olive oil industry, where the total waste generation is nearly 75% of the olive harvest [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis. X-ray diffraction analysis is a very important analytical technique commonly used in determining and verifying the crystalline phase of powdered materials and to identify the framework lattice of such particular materials [62,63]. e compared powder X-ray diffraction analysis of the BAC-P and BAC-Zn adsorbents (before and after adsorption) is shown in Figures 5(a) and 5(b), respectively.…”
Section: X-ray Diffractionmentioning
confidence: 99%
“…In batch mode operation, variables affecting the removal process such as pH, adsorbent dose, initial concentration of the contaminant, and contact time have also been optimised (El-Azazy et al 2020 ; El-Azazy et al 2021b ; El-Azazy et al 2021c ; Bardestani et al 2019 ; Beakou et al 2017 ; Kalderis et al 2017 ; Lenin Sundar et al 2021 ; Roy et al 2018 ; Turk Sekulic et al 2018 ; Zhao et al 2021d ). Variables such as fixed-bed height, flow rate, the particle size of the biochar adsorbent, pH, and concentration of the inlet solution are optimised in continuous mode operation (Biswas et al 2020 ; Blagojev et al 2019 ; Levio-Raiman et al 2021 ; Sivarajasekar et al 2018 ; Suárez‐Vázquez et al 2021 ).…”
Section: Environmental Remediationmentioning
confidence: 99%